2015
DOI: 10.1017/jsl.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Harrington’s Principle in Higher Order Arithmetic

Abstract: Let Z2, Z3, and Z4 denote 2nd, 3rd, and 4th order arithmetic, respectively. We let Harrington’s Principle, HP, denote the statement that there is a real x such that every x-admissible ordinal is a cardinal in L. The known proofs of Harrington’s theorem “$Det\left( {{\rm{\Sigma }}_1^1} \right)$ implies 0♯ exists” are done in two steps: first show that $Det\left( {{\rm{\Sigma }}_1^1} \right)$ implies HP, and then show that HP implies 0♯ exists. The first step is provable in Z2. In this paper we show that Z2 + HP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…So the consistency of (1) implies the consistency of sans-serifZ3+HP(boldL). By [, Theorem 3.2], sans-serifZ3+HP(boldL) implies that LZFC+``ω1V is remarkable”. By Proposition , ω2V is inaccessible in boldL.…”
Section: Characterizations Of the Strong Reflecting Property For Boldmentioning
confidence: 95%
See 1 more Smart Citation
“…So the consistency of (1) implies the consistency of sans-serifZ3+HP(boldL). By [, Theorem 3.2], sans-serifZ3+HP(boldL) implies that LZFC+``ω1V is remarkable”. By Proposition , ω2V is inaccessible in boldL.…”
Section: Characterizations Of the Strong Reflecting Property For Boldmentioning
confidence: 95%
“…In , we define 0# as the minimal iterable mouse and prove in Z4 that HP(L) is equivalent to “0# exists”. Theorem proves that these two definitions of 0# are equivalent in Z4.…”
mentioning
confidence: 99%
“…• Section 0.7 on Incompleteness in Nested Multiply Recursive Arithmetic and Two Quantifier Arithmetic. Related to Friedman's work, Cheng [21,24] gives an example of concrete mathematical theorems based on Harrington's principle which is isolated from the proof of the Harrington's Theorem (the determinacy of Σ 1 1 games implies the existence of zero sharp), and shows that this concrete theorem saying that Harrington's principle implies the existence of zero sharp is expressible in Second-Order Arithmetic, not provable in Second-Order Arithmetic or Third-Order Arithmetic, but provable in Fourth-Order Arithmetic (i.e., the minimal system in higher-order arithmetic to prove this concrete theorem is Fourth-Order Arithmetic).…”
Section: Harvey Friedman's Contributions Incompleteness Would Not Be Complete Without Mentioning the Work Of Harveymentioning
confidence: 99%
“…Eighth, we discuss some variants of R in the same language as L(R) = {0, ...,n, ..., + , × , ≤}. The theory R 0 is no longer essentially undecidable in the same language as R. 24 In fact, whether R 0 is essentially undecidable depends on the language of R 0 : if L(R 0 ) = {0,S, + , × , ≤} with ≤ defined in terms of +, then R 0 is essentially undecidable (Cobham first observed that R is interpretable in R 0 in the same language {0,S, + ,×}, and hence R 0 is essentially undecidable (see [65,127]). The theory R 1 is essentially undecidable since R is interpretable in R 1 (see [65, p. 62]).…”
Section: Generalizations Of G1 Via Interpretabilitymentioning
confidence: 99%
“…In this step, we shoot a club C through S via Baumgartner's forcing P B S such that if η is the limit point of C and 4 We still work in…”
Section: Step Threementioning
confidence: 99%